Pramipexole use and the risk of pneumonia - Ernst, Pierre (BioMed Central, 2012)
BACKGROUND: Patients with Parkinson's disease have an elevated risk of pneumonia and randomized trials suggest that this risk may be increased with the dopamine agonist pramipexole. It is uncertain whether pramipexole or other dopamine agonists increase the risk of pneumonia. METHODS: We used the United Kingdom's General Practice Research Database (GPRD) to identify users of anti-parkinsonian drugs, 40–89 years of age, between 1997 and 2009. Using a nested case–control approach, all incident cases hospitalised for pneumonia were matched with up to ten controls selected among the cohort members. Rate ratios (RR) and 95% confidence intervals (CI) of pneumonia associated with current use of dopamine agonists were estimated using conditional logistic regression, adjusted for covariates. RESULTS: The cohort included 13,183 users of anti-parkinsonian drugs, with 1,835 newly diagnosed with pneumonia during follow-up (rate 40.9 per 1,000 per year). The rate of pneumonia was not increased with the current use of pramipexole (RR 0.76; 95% CI: 0.57-1.02), compared with no use. The use of pramipexole was not associated with an increased rate of pneumonia when compared with all other dopamine agonists collectively (RR 0.85; 95% CI: 0.62-1.17). CONCLUSIONS: The use of pramipexole does not appear to increase the risk of pneumonia.